Search patterns and functional response of mites Phytoseiidae Amblyseius herbicolus (Chant) and Neoseiulus chilenensis (Dosse) preying on Tetranychus urticae (Koch) - SÁNCHEZ, MAURICIO; PÁRAMO, GABRIEL; CORREDOR, DARÍO (Revista Colombiana de Entomología, 1986)
The response of adult females of Tetranychus urticae in variable conditions of light and topography were examined in order to compare them with the searching patterns developed by Amblyseius herbicolus and Neoseiulus chilenensis mites in the same state. The searching area was wider for the A. herbicolus searching area. The functional response of the two predators to the variable density of T. urticae’s eggs was higher for N. chilenensis at low egg densities, but A. herbicolus was more effective at high egg densities A. herbicolus seems to need a complementary diet on top of the prey eggs.